2015
DOI: 10.1128/iai.00763-15
|View full text |Cite
|
Sign up to set email alerts
|

Neither Classical nor Alternative Macrophage Activation Is Required for Pneumocystis Clearance during Immune Reconstitution Inflammatory Syndrome

Abstract: c Pneumocystis is a respiratory fungal pathogen that causes pneumonia (Pneumocystis pneumonia [PcP]) in immunocompromised patients. Alveolar macrophages are critical effectors for CD4؉ T cell-dependent clearance of Pneumocystis, and previous studies found that alternative macrophage activation accelerates fungal clearance during PcP-related immune reconstitution inflammatory syndrome (IRIS). However, the requirement for either classically or alternatively activated macrophages for Pneumocystis clearance has no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 41 publications
1
17
0
Order By: Relevance
“…A recent study by Zhang et al demonstrates that mice lacking in either CAM or AAM responses still possess the ability to clear Pneumocystis (Zhang et al, 2015). By crossing IFNγR −/− mice or IL4rα −/− mice to RAG2 −/− animals, and then providing WT T cells by adoptive transfer, they demonstrated that in the setting of immune reconstitution inflammatory syndrome (IRIS), neither CAM or AAM were required for the clearance of Pneumocystis .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study by Zhang et al demonstrates that mice lacking in either CAM or AAM responses still possess the ability to clear Pneumocystis (Zhang et al, 2015). By crossing IFNγR −/− mice or IL4rα −/− mice to RAG2 −/− animals, and then providing WT T cells by adoptive transfer, they demonstrated that in the setting of immune reconstitution inflammatory syndrome (IRIS), neither CAM or AAM were required for the clearance of Pneumocystis .…”
Section: Discussionmentioning
confidence: 99%
“…By crossing IFNγR −/− mice or IL4rα −/− mice to RAG2 −/− animals, and then providing WT T cells by adoptive transfer, they demonstrated that in the setting of immune reconstitution inflammatory syndrome (IRIS), neither CAM or AAM were required for the clearance of Pneumocystis . However, while all strains were able to clear the organism, mice that lacked a CAM response (RAG2 −/− / IFNγR −/− ) had increased Pneumocystis-related immunopathologies (Zhang et al, 2015). Our results correspond with theirs in that the lack of signaling through the IL4rα to restrict AAM responses did not impact the clearance kinetics of the organism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lung injury associated with PCP-IRIS manifests with hypoxaemia, elevated lactate dehydrogenase and total protein in bronchoalveolar lavage fluid, weight loss and mortality [46, 47, 49]. A recent study using Rag1 −/− IFN-γR −/− or Rag1 −/− IL-4R −/− mouse models of IRIS demonstrated that the activation of M1 or M2 macrophages is not required for Pneumocystis clearance [50]. Furthermore, this study has shown that IFN-γ is a critical mediator in the exacerbated inflammatory response by decreasing the CD8 + Foxp3 + regulatory T-cell subset in PCP-IRIS [50].…”
Section: Immunopathology Of Iris Associated With Fungal Infectionsmentioning
confidence: 99%
“…A recent study using Rag1 −/− IFN-γR −/− or Rag1 −/− IL-4R −/− mouse models of IRIS demonstrated that the activation of M1 or M2 macrophages is not required for Pneumocystis clearance [50]. Furthermore, this study has shown that IFN-γ is a critical mediator in the exacerbated inflammatory response by decreasing the CD8 + Foxp3 + regulatory T-cell subset in PCP-IRIS [50]. Dectin-1 is involved in PCP-IRIS dependent lung injury, as antagonising dectin-1 signalling blocked the development of fungal IRIS [51].…”
Section: Immunopathology Of Iris Associated With Fungal Infectionsmentioning
confidence: 99%